PENGEMBANGAN KARAKTER KEAGAMAAN MELALUI PRAKTIK SHALAT JUMAT DI SMPN 1 SIMPENAN KAB. SUKABUMI - Faqih, Usman (Prodi PAI IAILM Suryalaya, 2022)
Islamic Education Learning no longer prioritizes absorption through the achievement of information from the subject matter, but rather prioritizes the development of the ability to apply or practice in real life. For that learning activities in the classroom needs to be improved through the demonstration method is done by the teacher, especially done by the students themselves, so it is expected that the quality of student worship can be improved. Demonstration method with role playing model is a way of presenting lesson by demonstrating or showing to learners a certain process, situation or object being studied, whether actual or artificial which is often accompanied by oral explanation. Implementation of learning in cycle I and II, done in three stages that first phase is to dig early knowledge of learners to practice procedure of prayer friday, both core stage is problem solving step, through activity of demonstration and role plying, and third is final stage Namely the stage of concluding the learning outcomes. The results of observation researchers, teacher activities and learners during the learning from cycle I to cycle II has a significant increase, namely the category being good and from the good category to be very good.